2020
DOI: 10.3390/insects11080483
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative, High Throughput Method to Identify Csd Alleles of the Honey Bee

Abstract: Applying instrumental insemination in closely related honey bee colonies often leads to frequent lethality of offspring causing colony collapse. This is due to the peculiarities of honey bee reproductive biology, where the complementary sex determination (csd) gene drives sex determination within a haplodiploid system. Diploid drones containing homozygous genotypes are lethal. Tracking of csd alleles using molecular markers prevents this unwanted event in closed breeding programs. Our approach described here i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It has also been suggested that csd may play a role in controlling the balance between inbreeding and outbreeding in honey bee reproduction [11,17,23]. Considering that heterozygosity at this gene is essential to generate vital females, several studies have investigated csd sequence diversity, demonstrating that a large number of functional alleles exist in all honey bee populations [21,[23][24][25][26][27][28][29]. These studies have mainly been carried out by Sanger sequencing the HVR from drones of different colonies, in order to maximize the probability of detecting the two alleles of the queen bees [23,24,28] or from workers after cloning the amplicons [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that csd may play a role in controlling the balance between inbreeding and outbreeding in honey bee reproduction [11,17,23]. Considering that heterozygosity at this gene is essential to generate vital females, several studies have investigated csd sequence diversity, demonstrating that a large number of functional alleles exist in all honey bee populations [21,[23][24][25][26][27][28][29]. These studies have mainly been carried out by Sanger sequencing the HVR from drones of different colonies, in order to maximize the probability of detecting the two alleles of the queen bees [23,24,28] or from workers after cloning the amplicons [25].…”
Section: Discussionmentioning
confidence: 99%
“…The level of diversity of this highly repetitive gene region has been investigated in different honey bee populations by several studies that mostly used Sanger sequencing of the HVR amplified from drones [21,[23][24][25][26]28,29]. These studies identified a high number of csd protein allele sequences that have been recently compiled in a scientific note [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using an appropriate set of primers, the entomological origin of honey can be determined to a certain degree, like distinguishing between species or, in some cases, even between some of the subspecies of honeybees [ 59 , 60 ]. While these sources do not seem directly applicable to queen breeding, genotyping of csd alleles using NGS technology yielded a diversity of these alleles within the colony [ 18 ]. Even if it may be difficult to envision such an approach in practice, it surely has a practical value in research.…”
Section: Discussionmentioning
confidence: 99%
“…The successful extraction of DNA from clipped wings and subsequent genotyping were reported in the past [ 13 , 14 , 15 , 16 , 17 ]. Recent research demonstrated the efficient high throughput method to identify csd alleles of the honeybee queens using wing clippings coupled with a next-generation sequencing approach [ 18 ]. Though successful, there is still a requirement to wait with wing clipping until mating flights are completed.…”
Section: Introductionmentioning
confidence: 99%